Increasing Transmitted Power With Cost Mitigation via Modified EHV Power Lines in Egyptian Grid - Ahmed Taleb Mohamed; Ahdab El-Morshedy; Elsayed Tag-Eldin; Ahmed Emam; Mohamed Mahmoud Samy (IEEE Access, 2023)
The main goal of this work is to mitigate the cost of modified EHV line of the Egyptian transmission network. The existing HVAC line is replaced by four configurations, the first one is double circuit operating with an AC potential and bipolar DC circuit of B1500 kV while the second one is a double circuit operating with 500 kV AC circuit and B1500 kV bipolar circuit with required conductor and/or tower modification. The third one is a double DC circuit working with two B1500 kV. The fourth configuration is working with three B1500 kV bipolar circuits. The study shows the increase in transmitted power percentage and the cost mitigation for each suggested configuration relative to the existing AC line. Starting from the break-even distance of each configuration to 500 km, each configuration result will be analysed. Configuration 1 has the shortest break-even distance at 148 km. The power percentage increased from 3% to 5% and the cost mitigated by 22.17%. Break-even distance of configuration 2 is 171 km. Configuration 2 has power percentage increase from 30% to 32% and the cost reduced by 22.45%. Above 212 km break-even distance, configuration 3 has the best cost mitigation percentage of 28.60% and the power percentage increased from 7% to 9%. Configuration 4 records the highest increase in the power percentage range of 60% to 64% and cost reduction of 27.72% after 221 km break-even distance.